Application of the Teaching at the Right Level (TaRL) Approach to Improve Learning Outcomes of Class VII Students at Sis Al-Jufri SMPN Madani Integrated Model, Palu - Musfira, Musfira; Rochaminah, Sutji; Sudarsono, Sudarsono (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research aims to obtain a description of the application of the Taching at The Right Level approach to improve the learning outcomes of class VII Sis Al-Jufri students regarding Data and Data Presentation. The research subjects were 32 class VII students, Sis Al-Jufri, SMPN Model Terpadu Madani Palu. The data collection technique in the form of a written test was carried out twice, namely cycle I and cycle II.  The method used is classroom action research, each cycle consisting of several stages, namely planning, implementing actions, observing and reflecting. Based on the research results, the average student learning outcomes increased from cycle I to cycle II. In cycle I, the average student learning outcome reached 75 with a completion percentage of 59%. In cycle II there was an increase where the average student learning outcome became 86 with a completion percentage of 81%. In conclusion, the application of the TaRL approach can improve the mathematics learning outcomes of class VII students at Sis Al-Jufri SMPN Model Terpadu Madani Palu.